Psoriasis: new comorbidities - Jackson Machado-Pinto; Michelle dos Santos Diniz; Nádia Couto Bavoso (Sociedade Brasileira de Dermatologia, 2016)
Abstract Psoriasis is a chronic inflammatory disease associated with several comorbidities. A few decades ago, it was considered an exclusive skin disease but today it is considered a multisystem disease. It is believed that 73% of psoriasis patients have at least one comorbidity. Studies have demonstrated the association of psoriasis with inflammatory bowel disease, uveitis, psychiatric disorders, metabolic syndrome and its components and cardiovascular diseases. The systemic inflammatory state seems to be the common denominator for all these comorbidities. This work aims at presenting a review of the current literature on some new comorbidities that are associated with psoriasis as osteoporosis, obstructive sleep apnea and chronic obstructive pulmonary disease. While there is still controversy, many studies already point to a possible bone involvement in patients with psoriasis, especially in the male group, generally less affected by osteoporosis. Psoriasis and chronic obstructive pulmonary disease present some risk factors in common as obesity, smoking and physical inactivity. Besides, both diseases are associated with the metabolic syndrome. These factors could be potential confounders in the association of the two diseases. Further prospective studies with control of those potential confounders should be developed in an attempt to establish causality. Existing data in the literature suggest that there is an association between obstructive sleep apnea and psoriasis, but studies performed until now have involved few patients and had a short follow-up period. It is, therefore, premature to assert that there is indeed a correlation between these two diseases.